Comparables Pricing - Murfin, Justin; Pratt, Ryan (Review of Financial Studies, 2019)
Finance professionals commonly set prices based on the analysis of recently closed, comparable transactions. Using data on syndicated loans, we exploit the lag between loans’ closing dates and their inclusion in a widely used comparables database to identify the effect of past transactions on new transaction pricing. Comparables pricing is an important determinant of individual loan spreads, but a failure to account for overlap in information across loans leads to pricing mistakes. Comparables used repeatedly are overweighted as they develop redundant channels of influence on later transactions. Market conditions prevailing at the time a comparable was priced also unduly influence subsequent loans. Received May 23, 2016; editorial decision January 23, 2018 by Editor Robin Greenwood.